The conjuring 4. Last rites [videorecording (DVD)] - Goldberg, Ian (Ian B.); Naing, Richard; Johnson, David Leslie; Wan, James, 1977-; Wilson, Patrick, 1973-; Farmiga, Vera; Tomlinson, Mia; Hardy, Ben, 1991-; Coulter, Steve; Calder, Rebecca (Actor); Cowan, Elliot, 1976-; Gadsdon, Beau; et al. (Warner Bros., 2025)
"Inspired by the harrowing true story of the Smurl family haunting, The Conjuring: Last Rites marks the final appearance of Patrick Wilson and Vera Farmiga as Ed and Lorraine Warren. When a quiet Pennsylvania home becomes ground zero for a relentless supernatural siege, not everyone will make it out unscathed."--